PENGARUH FINANCIAL ACTION TASK FORCE ON MONEY LAUNDERING TERHADAP TERBENTUKNYA UNDANG-UNDANG PENCUCIAN UANG DI INDONESIA - Armanda, Rizky; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research aims to describe the influence of FATF in the formation of moneylaundering legislation in Indonesia. Money laundering has become a global issue thatthreatens economic system in a country and internationally also. Big impact of moneylaundering require the more interest of countries in the world to quickly establish acooperation in an effort to eradicate money laundering.According to Clive Archer in generally, International Organization is a pattern ofrelations of cooperation accross the borders of its member countries have the same goalto achieve. FATF is an Inter Governmental Organization (IGO). FATF has a role indetermining the policies and issuing recommendations to eradicate money launderingwhich should be adopted by all countries. FATF requires each state to criminalizemoney laundering. In this case also uses the role theory of K.J. Holsti to describe howInternational Organizations like a FATF, has a role in international relations.The result shows that the formation of money laundering legislation in Indonesianot in spite of the influence of FATF with various forms of pressures on Indonesia toimmediately do the criminalization of money laundering, such as: FATF put Indonesiato the list of reviews and list of Non Cooperative Countries and Territories (NCCT’s)accompanied by the threat of sanctions to Indonesia if it doesn’t immediately complywith the rules apllied by the FATF. In the end, for the first time Indonesia docriminalization of money laundering with legislated No. 15/ 2002.Keywords: crime, FATF, Indonesia, influence, money laundering